To simplify the expression (78^8)^6 using the Power Rule of Exponents, we multiply the exponents:
(78^8)^6 = 78^(8*6) = 78^48
Use the Power Rule of Exponents to simplify the expression (78^8)^6. (1 point)
3 answers
That's wrong
I apologize for the incorrect response. I made a mistake.
To simplify the expression (78^8)^6 using the Power Rule of Exponents, we multiply the exponents:
(78^8)^6 = 78^(8*6) = 78^48
So, the simplified expression is 78^48.
To simplify the expression (78^8)^6 using the Power Rule of Exponents, we multiply the exponents:
(78^8)^6 = 78^(8*6) = 78^48
So, the simplified expression is 78^48.